The subjectivity of pestilence in view of the COVID-19 - Mochama, Amos (Research Journal in Advanced Humanities, 2020)
The global outbreak of the COVID-19 has occasioned disruptions to all people’s diverse cultures across the world. Faced with one of the greatest challenges in decades, individuals, families, communities, corporate bodies and governments have been forced to react by adopting new and stringent measures, aimed at combating this highly communicable disease. Meetings such as funerals, weddings, classes, political gatherings, religious congregations, sporting events and all other events that require physical human contact, have either been indefinitely postponed or the number of people attending such functions as funerals reduced to a maximum of fifteen in Kenya. It is against this backdrop that this paper examines how responses to the global pestilences trigger disruptions to people’s culture resulting in adoption of new sets of ways of life, that are a complete departure from the known conventional lifestyles. The adoption of digital technology has helped alleviate the harsh containment measures around the globe in partial discharge of essential public functions as opposed the otherwise effective physical meetings. The paper argues that the changes occasioned by the discovery of the COVID-19 may not be abandoned altogether even after its consequent containment.